The Influence Of Social Interaction, Skills, And Supervision On The Performance Of Employees At Batu Bara District Human Resources - Hadi, Sofian; Desfika, Rama; Azwar, Muhammad; Sirait, M. Sumihar; Safrida, Safrida; Riana, Zenni (Jurnal Ilmiah Manajemen dan Bisnis (JIMBI), 2024)
This examination means to determine the impact of social association, abilities and management on the presentation of representatives of the Batu Bara Regime Faculty and HR Improvement Organization. The example in this examination was all representatives of the Batu Bara Rule Faculty and HR Improvement Organization, adding up to 49 individuals. The information examination strategy in this exploration is Various Direct Relapses. Social interaction has a positive and significant impact on employee performance, according to the findings of this study: employee performance is partially and significantly impacted by skills; fractional oversight significantly affects representative execution; and social cooperation, abilities and oversight at the same time affect representative execution.